Peran Pemerintah Kalurahan Dalam Pengendalian Stunting (Studi Khasus Kelurahan Giriharjo Kapanewon Panggang) - Muharyanto, Muharyanto; Muryanto, Febriana; Suindartini, Suindartini (CV. ITTC INDONESIA, 2024)
This study explores the role of the local government in Giriharjo Village, Panggang Subdistrict, Gunungkidul Regency, in controlling stunting, aiming to understand how government interventions can create sustainable and high-quality human resources. Using a qualitative methodology with a descriptive design, the research was conducted in Giriharjo Village, purposefully selected due to the high prevalence of stunting. The research subjects included village officials, medical personnel, and local community members directly involved in stunting prevention programs. Data were collected through in-depth interviews, participatory observation, and document studies, and then analyzed thematically to identify relevant patterns and themes. The findings indicate that the Giriharjo Village government has implemented various policies and programs focusing on stunting prevention, including allocating funds for health and nutrition programs and raising community awareness through outreach and support. However, the study also revealed challenges such as limited resources and funding that affect the effectiveness of these programs. Recommendations include enhancing outreach efforts, providing training for healthcare workers, and optimizing the use of village funds to support sustainable stunting prevention programs.